A New Facility for Market Access Countries : The Short-Term Liquidity Facility -- proposed decision. (Policy Papers; Policy Paper, 2008)
This supplement sets forth the proposed decision that is needed to establish the Short-Term Liquidity Facility ('SLF') proposed in the main paper. It also summarizes key aspects and implications of this decision, and reviews the applicability to the SLF of other Fund policies.